A Comparitive Study between Kapandji and Extra-Focal Fixation in Extra Articular Distal Radius Fractures (Global Journal of Medical Research, 2021)
Purpose: To assess and compare the radiological and functional outcome of extra articular distal radius fractures treated by either Kapandji technique or extra-focal technique of K wire fixation. Method: From January 2018 to March 2020, 60 patients with extra articular distal radius fracture were included in this prospective study after obtaining informed consent regarding the same. Out of these 30 went under extra-focal technique and 30 went under Kapandji technique of K wire fixation. After surgery in both groups we immobilized the limb in below elbow cast for 5 weeks after which cast was removed and k-wires were removed. Radiographs were taken at 1 month, 3months and 6 months post operatively. All patients followed proper physiotherapy protocol after 5 weeks of surgery.
Keywords: extra articular distal radius fracture; extra-focal technique; kapandji technique; K wire fixation; gartland and werley score